Nanoporous Materials III : proceedings of the 3rd International Symposium on Nanoporous Materials, Ottawa, Ontario, Canada, June 12-15, 2002 /: proceedings of the 3rd International Symposium on Nanoporous Materials, Ottawa, Ontario, Canada, June 12-15, 2002. (2002) - Unknown
No abstract available